Research in organizational change and development. Vol. 20 - Shani, Abraham B. (Rami); Pasmore, William A.; Woodman, Richard W. (Research in organizational change and development,, 2012)
For 25 years Research in Organization Change and Development has provided a special platform for scholars and practitioners to share new research-based insights. Volume 20 continues the tradition of providing insightful and thought provoking chapters. Some papers bring new perspectives to classic issues in the field such as survey feedback, learning and change leadership. Others explore new territories, such as the role of computer mediated communication and its impact on organizational change and development, action learning and the role that it can play in the development of scholar-practitioners, the creation of actionable knowledge about organization development and change, and the role that ODC knowledge can play in assisting organizations to succeed within the new paradigm of sustainable value creation. Together, these chapters make an especially timely and intriguing collection. It represents a unique blend of theory and practice, intervention and research, revisiting traditional practices and introducing emerging new ones, providing multidisciplinary perspectives on current issues in the field and even a proposed new paradigm for organization development and change.